AMERICAN-BRITISH RELATIONS IN THE CONTEXT OF THE FORMATION OF THE INTERSTATE ASSOCIATION AUKUS - Andrii Hrubinko (Американська історія і політика)
The article presents the results of a study of the genesis of US-British relations in the context of the historical and political peculiarities of the formation of the interstate association AUKUS.